Adoption of Recommended Practices by Fish Processing Plants in Kerala - Mohan, Braj; D.P., Singh; R., Thiagarajan (Fishery Technology, 2025)
This paper attempts to explore the extent of adoption of practices identified by the Central Institute of Fisheries Technology for fish freezing and fish processing plants and the influence of socio-economic factors on the adoption. Practices such as sanitary conditions of processing unit, maintaining temperature of cold storage, personal hygiene of workers and glazing the material before/after freezing showed higher level of adoption. However, use of deodorants, use of recommended packing materials for individually quick frozen shrimps and use of recommended containers for transportation showed lower level of adoption.